Gamification with video games in Spanish as Foreign Language - Espinar Ruiz, Gregorio (Revista Letras Raras, 2023)
The world of language teaching and acquisition, just like any other sector of society, is currently going through an adaptation process due to the appearance of the Internet and new technologies. The first goal of this article is to study the possibilities within a Spanish language class of one of the most emblematic objects of technological development: video games. To achieve this, we will first examine the theoretical framework in which the concepts ‘game’, ‘serious game’, ‘videogame’ and ‘gamification’ are analyzed and later present examples of videogames that are being used increasingly often in the classroom. The second objective, which concludes the article, is the elaboration of a gamified educational proposal consistent with the creation of an in-class digital gamebook using user-friendly and easy access software.